2018
DOI: 10.1016/j.jtho.2018.08.747
|View full text |Cite
|
Sign up to set email alerts
|

P1.04-32 Phase I/II Study of the A2AR Antagonist NIR178 (PBF-509), an Oral Immunotherapy, in Patients (pts) with Advanced NSCLC

Abstract: Background: ATP is catabolized to adenosine in the tumor microenvironment, leading to excess adenosine and immunosuppressive effects via immune checkpoint protein adenosine 2A receptor (A2AR). NIR178 is an oral A2AR antagonist that selectively binds and inhibits A2AR, reactivating T cell-mediated antitumor immune response. This Phase I/II study evaluated NIR178 in previously treated pts with advanced NSCLC (NCT02403193). Method: Pts (ECOG PS 0-1) had received 1 prior line of therapy; EGFR/ALK pts had failed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…在临床试验阶段,靶向CD39或CD73的单克隆抗体和小分子抑制剂也有显著的治疗效果。CD39抑制剂ES002023通过稳定细胞外ATP和抑制肿瘤微环境内腺苷的合成来恢复抗肿瘤免疫(NCT05075564)。CD73选择性抑制剂AB680具有良好的药代动力学特性,已进入Ⅰ期临床试验。在一项Ⅰb/Ⅱ期临床试验(NCT03381274)中,抗CD73单克隆抗体MEDI9447联合酪氨酸激酶抑制剂奥希替尼在既往接受治疗的晚期EGFR突变NSCLC患者中具有中等活性和可接受耐受性 [ 79 ] 。目前,进入临床试验的A2aR抑制剂有CPI-444、NIR178、AZD4635等。一项Ⅰ/Ⅱ期临床试验(NCT02403193)显示,24例晚期NSCLC患者对NIR178具有良好的耐受性,不良反应可控且无第四级药物相关不良事件 [ 80 ] 。…”
Section: 针对抑制肿瘤获得性免疫的干预策略unclassified
“…在临床试验阶段,靶向CD39或CD73的单克隆抗体和小分子抑制剂也有显著的治疗效果。CD39抑制剂ES002023通过稳定细胞外ATP和抑制肿瘤微环境内腺苷的合成来恢复抗肿瘤免疫(NCT05075564)。CD73选择性抑制剂AB680具有良好的药代动力学特性,已进入Ⅰ期临床试验。在一项Ⅰb/Ⅱ期临床试验(NCT03381274)中,抗CD73单克隆抗体MEDI9447联合酪氨酸激酶抑制剂奥希替尼在既往接受治疗的晚期EGFR突变NSCLC患者中具有中等活性和可接受耐受性 [ 79 ] 。目前,进入临床试验的A2aR抑制剂有CPI-444、NIR178、AZD4635等。一项Ⅰ/Ⅱ期临床试验(NCT02403193)显示,24例晚期NSCLC患者对NIR178具有良好的耐受性,不良反应可控且无第四级药物相关不良事件 [ 80 ] 。…”
Section: 针对抑制肿瘤获得性免疫的干预策略unclassified
“…Oral administration of PBF-509 (15 or 30 mg/kg/day) significantly reduced the tumor burden of mice in both models [18]. A phase I/II study of PBF-509 both alone and in combination with anti-PD-1 mAb PDR001 in non-small cell lung cancer patients was started in October 2015 (NCT02403193); the results showed that the compound was well tolerated, and clinical benefit was observed in immunotherapy-exposed and -naive patients, irrespective of the PD-L1 status [62].…”
Section: Pbf-509mentioning
confidence: 99%